Economic analysis of vineseed fertirrigation compared to potassium in corn culture - Muniz, Adjana Martins de Freitas; Cabral Filho, Fernando Rodrigues; Andrade, Christiano Lima Lobo de; Teixeira, Marconi Batista; Alves, Daniely Karen Matias; Silva, Edson Cabral da (Brazilian Journal of Science, 2023)
Corn is a product of great economic relevance and requires adequate replacement of nutrients in the soil to achieve good results in terms of productivity, such as Potassium (K) which is the second nutrient most absorbed by plants and accumulates in the grains and plant stalks. On the other hand, vinasse is a residue from the sugar and alcohol agroindustry rich in K that has been used in the fertirrigation of crops such as sugarcane and corn and has shown satisfactory results as an increase in productivity. The study aimed to analyze the economic viability of fertirrigation with vinasse compared to K in corn. Experimental test was carried out, in the experimental area Pulveriza Soluções Agricolas, in Rio Verde, Southwest region, Goiás, Brazil. Sowing took place in March 2022, where AS1820 hybrid corn was used. Before planting, seed treatment was performed with Standak® Top (200 mL 100 kg-1) + Policote Seeds Titanium Verde® (3 mL kg-1), spacing 0.45 m and 3 plants per m, 65,000 plants per hectare. With the intention of treating the seeds, Standak® Top (200 mL 100 kg-1) + Policote Seeds Titanium Verde® (3 mL kg-1) and vinasse were applied. Through the analysis of cost, and productivity comparing the application of commercial K in comparison to vinasse as well, as both associated and double application of vinasse, it was considered that the single application of vinasse presented lower financial cost and greater profitability in relation to all the others, thus making it possible to conclude that this treatment is economically viable compared to the treatment with commercial potassium and the combination of both.